Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1896)
Demorest's Family Magazine. May 1896. Vol. 32, no. 7. Life in a Japanese Bungalow -- Arbutus -- Venezuela and Her Debatable Boundary -- A Knight of the Nets -- Cuba Struggles for Independence -- The Legend of the Gardener -- A Mighty Power for Good -- First Efforts for Success -- Society Fads -- Afternoon Tea with "La Loie" -- Our Girls: A Day at Vassar -- Home Art and Home Comfort: Furnishing the Summer Home -- Sanitarian: Headaches -- The World's Progress -- About Women -- Mirror of Fashions: Furnishing in Style --
Mme Demorest's Mirror of Fashions
Digitized from original print, Valdosta State University Archives and Special Collections, March 2, 2017.
Keywords: Women's History; Fashion; Periodicals; Dressmaking; Magazines